Effectiveness of Schema Therapy on Components of Love and Emotional Empathy in Single Women with Fear of Marriage - Behiroz , Azar; Khayatan, Felor; Yousefi , Zahra (Psychology of Woman Journal, 2025)
Objective: This study aimed to examine the effectiveness of schema therapy on the components of love and emotional empathy in single women with a fear of marriage. Materials and Methods: The research method was semi-experimental with a pretest-posttest and follow-up design with a control group. The statistical population included all female students at Payame Noor and Azad universities in Semirom in 2023. Participants were selected based on inclusion and exclusion criteria. A total of 30 individuals were chosen through convenience sampling and randomly assigned to experimental and control groups (15 individuals in each group). A pretest was administered to both groups. The experimental group received schema therapy over 8 sessions, while the control group did not receive any intervention. Data were collected using the Sternberg Love Components Questionnaire (1996), the Baron-Cohen and Wheelwright Emotional Empathy Questionnaire (2004), and the Delkhamoosh Fear of Marriage Questionnaire (2007). The data were analyzed using repeated measures analysis of variance (ANOVA) in SPSS version 23. Findings: The results showed that schema therapy significantly increased the components of love and emotional empathy in single women with a fear of marriage. The therapeutic effects were maintained during the follow-up phase (F = 9.95, P < 0.01). Conclusion: Based on the findings of this study, schema therapy can be utilized to enhance the components of love and emotional empathy in single women with a fear of marriage.